EFFECT OF THE EXCITED VOLTAGE RISE TIME ON THE CORONA DISCHARGE CHARACTERISTICS - ALi Hussein; Qais Algwari (College of Education for Pure Sciences, 2023)
In this paper, the rise time of the exciting voltage on the DC corona discharge characteristics in a coaxial electrode system is presented. The current one-dimensional simulation study focused on the distribution of the plasma species (ions and electrons as well as the excited atoms) during two different times of the applied voltage climb was classified as a fast rise time (615 ns) and a slow rise time (2710 ns). The growth time of the corona excited voltage was controlled by the external feed RC circuit that connected with the central electrode. The simulation results reveal that the corona inception which occurs at a fast rise time produces more dense plasma charged species, while the density of the excited atoms is not much affected by the applied voltage climb time. The density of excited atoms tends to depend on the rise time of the exciting voltage at the steady state.